2016
DOI: 10.4012/dmj.2014-341
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite element analysis of stress distribution in inlay-restored mandibular first molar under simultaneous thermomechanical loads

Abstract: Functional occlusal loads and intraoral temperature changes create stress in teeth. The purpose of this study was to evaluate the impact of simultaneous thermomechanical loads on stress distribution related to inlay restored teeth by three-dimensional finite element analysis. A mandibular first molar was constructed with tooth structures, surrounding bone and inlays of Type II gold alloy, ceramic, and composite resin. Stress patterns on the restorative materials, adhesive resin, enamel and dentin were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…These observations are consistent with the study [33] which showed that the narrow structure at the crown tip causes high stresses and bending in the crown. The present numerical results also match other studies where high stresses were reported on the enamel surface within top 1/3 rd region of the crown [19,36,45,48].…”
Section: Effect Of Loading Anglesupporting
confidence: 91%
“…These observations are consistent with the study [33] which showed that the narrow structure at the crown tip causes high stresses and bending in the crown. The present numerical results also match other studies where high stresses were reported on the enamel surface within top 1/3 rd region of the crown [19,36,45,48].…”
Section: Effect Of Loading Anglesupporting
confidence: 91%
“…[ 9 ] The occlusal contact points on the crown were subjected to a load of 200 N to simulate normal occlusal forces. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Different simulated material properties (Young’s modulus (E) and Poisson’s ratio values) were generated, based on data from the literature (Table 2). 15,17,19 Cross-sections of root canal were created from the apex at intervals of 1.0 mm. To visualize the stress distributions and magnitudes in the models, the data were transformed into color graphics.…”
Section: Methodsmentioning
confidence: 99%